Association between maternal infertility treatment and child neurodevelopment: findings from the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study in Miyagi and Iwate Prefectures, Japan. Issue 6 (7th June 2022) - Noda, Aoi; Ishikuro, Mami; Obara, Taku; Murakami, Keiko; Ueno, Fumihiko; Matsuzaki, Fumiko; Onuma, Tomomi; Watanabe, Zen; Shiga, Naomi; Iwama, Noriyuki; Hirotaka, Hamada; Otsuka, Tatsui; et al.
Abstract : Objectives: This study aimed to examine the association between infertility treatment and neurodevelopment in children at 2 and 3.5 years of age. Design: Prospective cohort study. Setting and participants: The study population consisted of mother–child pairs who participated in the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study in Miyagi and Iwate Prefectures, Japan. Pregnant women were recruited in obstetric clinics or hospitals and their children were followed up by the questionnaire. Outcome measures: The children's neurodevelopmental outcomes were assessed at 2 and 3.5 years of age using the Ages and Stages Questionnaire, third edition (ASQ-3), which consists of questions on five developmental domains. We performed a multivariate logistic regression analysis of the association between infertility treatment (including ovulation induction (OI), artificial insemination with husband's sperm (AIH) and assisted reproductive technology (ART)) and the clinical range of ASQ-3. Results: Of 9655 mother–child pairs, 273 (2.8%) and 487 (5.0%) were conceived through OI/AIH and ART, respectively. The odds of having developmental delays at 2 years of age were higher in children conceived through OI/AIH (OR, 1.36; 95% CI 1.00 to 1.85) and ART (OR, 1.36; 95% CI 1.07 to 1.72) than in those conceived naturally. Additionally, OI/AIH and ART were significantly associated with communication (OR, 1.93; 95% CI 1.25 to 2.98) and gross motor (OR, 1.50; 95% CI 1.08 to 2.09) delays, respectively. There were no statistically significant differences in the odds of having developmental delays at 3.5 years of age in children conceived through OI/AIH (OR, 1.13; 95% CI 0.79 to 1.61) and ART (OR, 1.03; 95% CI 0.78 to 1.37). Conclusion: In this study, we found a significant association between infertility treatment and children's neurodevelopment at 2 years of age, whereas no statistically significant differences were found at 3.5 years of age.